Evidence based medicine for improving skills in pharmacotherapy follow up - Delgado-Pérez, Gladys M. (2015)
In learning Pharmacotherapy Follow up (PF), an aspect is to assess correctly the clinical patient data and consuming drugs, and applying the "Evidence Based Medicine" (EBM), it is achieved that every decision to take, be supported by research that proves to be the most appropriate from the perspective of rationality. The aim of this study was to improve the skills of undergraduate students in the Pharmacotherapy Follow up, in the search for scientific drug information using the EBM. It is a quasi-experimental, prospective, longitudinal analytical design, developed in two stages: first with the traditional methodology and then with the EBM, structuring clinical questions through the PICO strategy. With the EBM were recovered 74% of literatures higher quality of evidence (meta-analysis, clinical trials, cohort studies, case series, expert opinion), against to recoveries with the traditional methodology (26%), recovering systematic reviews mainly. The effectiveness to detect Drug-Related Problems (DRP), when EBM was applied, was 58%, versus 42% with traditional method; besides, the effectiveness to raise pharmaceutical interventions with EBM method was 55% versus 45% with the traditional. Was concluded that students managed to improve skills detecting DRP in 20% and while in the pharmaceutical intervention in 8%.